2006
DOI: 10.3748/wjg.v12.i2.287
|View full text |Cite
|
Sign up to set email alerts
|

Role of N-acetylcysteine in rifampicin-induced hepatic injury of young rats

Abstract: NAC protects young rats against RMP-induced oxidative hepatic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 27 publications
2
27
1
Order By: Relevance
“…Anti-tuberculosis drugs may have also damaged mitochondria, an intracellular organelle that produces energy, whose dysfunction releases excessive amount of oxidants which in turn injures hepatic cells (Shah, 1999). Studies have indicated the existence of a strong correlation between hepatic injury and oxidative stress in experimental animals treated with anti-tuberculosis drugs Rana et al, 2006). Other studies have shown that anti-tuberculosis drugs generally act as inducers of hepatic cytochrome P 450 enzymes (Trevor et al, 2004;Vuilleumier et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Anti-tuberculosis drugs may have also damaged mitochondria, an intracellular organelle that produces energy, whose dysfunction releases excessive amount of oxidants which in turn injures hepatic cells (Shah, 1999). Studies have indicated the existence of a strong correlation between hepatic injury and oxidative stress in experimental animals treated with anti-tuberculosis drugs Rana et al, 2006). Other studies have shown that anti-tuberculosis drugs generally act as inducers of hepatic cytochrome P 450 enzymes (Trevor et al, 2004;Vuilleumier et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The plasma half life of AcHz (metabolite of INH) is shortened by RMP and AcHz is quickly converted to its active metabolite by increasing the oxidative elimination rate of AcHz, which is related to the higher incidence of liver necrosis caused by INH and RMP in combination (Hussain et al, 2003). Rats have been used successfully to investigate INH and RIF-induced hepatotoxicity models (Tasduq et al, 2005;Pal et al, 2006;Victorrajmohan et al, 2005;Rana et al, 2006). Therefore, we selected rats to study the hepatotoxic effect of antitubercular drugs and hepatoprotective action of H. corymbosa.…”
Section: Resultsmentioning
confidence: 99%
“…[109][110][111] Anti-tubercular drugs also induce hypercholesterolemia that might be due to increased uptake of LDL from the blood, by the tissues. [112,113] Hepatitis has been reported to occur 0.46% of individuals undergoing anti-tubercular therapy and receiving anti-tubercular drugs. The rate of hepatotoxic reaction was much higher in Indian patients as compared to that reported from developed countries.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%